The importance of sensorial empathy and the language of touch when crafting textiles for people who are visually impaired. Issue 1 (1st March 2020) - Hunt, Kevin; Piper, Anna; Worker, Georgie
AbstractThis article reflects upon a pilot project crafting textile samples/prototypes for people who are visually impaired. It explores the role that sensorial empathy and further understanding of the language of touch play in the textile crafting process for makers working with people who are visually impaired, and that aesthetic and experiential textiles (while important to all) are especially important to people who are visually impaired. The project undertakes craft research in an area that is generally overlooked by textile designers. The makers/participants were sighted second-year undergraduate textile design students at Nottingham Trent University and the end users, who acted as informants, were service users at My Sight Nottinghamshire (a charity in the United Kingdom addressing visual impairment). The project is situated within human-centred design, with a focus on physically intuitive designs crafted for people with visual impairments. The application and usage of the samples/prototypes are aimed at inclusivity, with engagement centred primarily around haptic touch, and so looking at the textiles may not reveal their potential application, which becomes more apparent through physical engagement. The project was inspired by work within sensory studies, including the concept of sensorial empathy, and research relating to the language of touch through tactile encounters with art objects from a visually impaired perspective. The methods used in the project drew upon empathic design processes, which were informed by sensory ethnography ‐ particularly 'emplacement' and the holistic consideration of mind, body and place ‐ and selected aspects of social haptics, particularly 'environmental description'. Recommendations include further development of the language of touch to support textile craft when working with people who are visually impaired and further consideration of 'grounding' as a concept regularly described by the informants.